2005
DOI: 10.1111/j.1600-6143.2005.00864.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus Antibody Status and Survival After Renal Transplantation: Meta-Analysis of Observational Studies

Abstract: The natural history of hepatitis C virus (HCV) among patients after renal transplantation (RT) remains incompletely defined. We conducted a systematic review of the published medical literature on the impact of hepatitis C antibody status on survival of patients who received RT. We used the random effects model of DerSimonian and Laird to generate a summary estimate of the relative risk (RR) for mortality and graft loss with HCV seropositivity across the published studies.We identified eight clinical trials (6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
153
0
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 238 publications
(167 citation statements)
references
References 43 publications
9
153
0
5
Order By: Relevance
“…Compared to non-HCV-infected CKD Stage 4/5 patients, HCV-infected CKD Stage 4/5 patients have poor graft survival and higher overall mortality outcomes following renal transplantation (Fabrizi, Martin, et al 2005;Terrault and Adey 2007).…”
Section: Patients With Advanced Chronic Kidney Diseasementioning
confidence: 99%
“…Compared to non-HCV-infected CKD Stage 4/5 patients, HCV-infected CKD Stage 4/5 patients have poor graft survival and higher overall mortality outcomes following renal transplantation (Fabrizi, Martin, et al 2005;Terrault and Adey 2007).…”
Section: Patients With Advanced Chronic Kidney Diseasementioning
confidence: 99%
“…Increase in the prevalence of CKD, and high rates of HBsAg and Anti-HCV seropositivity seen in hemodialysis patients have rendered these infections important in CKD population. It is known that, in CKD, especially in patients receiving dialysis, and in renal transplant patients, HBV and HCV infections are independent causes of morbidity and mortality (17)(18)(19)(20)(21). The risk of the development of cirrhosis and hepatocellular carcinoma due to chronic HBV and HCV infections, the risk of transmission to the other patients and medical personnel in hemodialysis centers, and the necessity for close follow up in renal transplant patients during immunosuppressive treatment are the major problems associated with HBV and HCV infections.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that hemodialysis treatment is preferred at the rate of 87.3% while initiating RRT in our country, it can be proposed that the increased Anti-HCV seropositivity in hemodialysis patients compared to CKD patients without RRT may be associated with the hemodialysis modality. (19,20). In addition, it is known that, HCV infection occurs more commonly in CKD and is associated with an increase in the risk of end stage renal disease (15,22).…”
Section: (100)mentioning
confidence: 99%
“…Some studies report a lower patient survival rate of HCVpositive kidney recipients in comparison to HCVnegative recipients, whereas other studies report similar outcomes between these two groups. 3,4 There is a four-to seven-fold increase in HCV viremia after transplantation when compared to the pretransplant period. It has been suggested that the spectrum of immune response to the virus in immunosuppressed patients is as variable as in immunocompetent patients.…”
Section: Introductionmentioning
confidence: 99%